MULTIMODAL ANALYSIS: PEDAGOGICAL REPRESENTATION OF VISUAL IMAGES IN EFL TEXTBOOKS - Lestari, Anisa Rimba (2022)
Within the educational context, multimodality and multimodal literacy have been studied as a goal of literacy education, a fundamental aspect of the classroom's semiotic activities, and instructional materials that aim to promote learning. As a result, textbooks nowadays are highly visual in their design. In language teaching and learning, visual images can act as communication tools and powerful elements in building students' knowledge about the outside world, creating a social setting that cannot be formed in a classroom environment, and giving real-life examples. The purpose of this research is to investigate the pedagogical representation of visual images from the representational, interactive, and compositional meanings of visuals in EFL textbooks. This research adopts the visual grammar framework proposed by Kress and van Leeuwen (2006). The data in this research cover the visual images from two Indonesian EFL textbooks for 10-grade students. The findings suggest that representationally, the images in EFL textbooks are utilised to help students to understand the content and social interaction and to transfer conceptual knowledge by matching the image with its real-world referent following the topics in the textbooks. Interactively, social relations and power equality exist between the image and the viewer. Compositionally, the images have an essential role in language learning that help students to engage effectively with the exercises in the textbooks, and the EFL textbooks construct the conceptual meaning of the text from the Top/Bottom (Ideal/Real) composition.